Imagination and the Imaginary: an Approach in Concept and Terminology - بولحواش , سعاد; بودربالة , الطيب (Milev Journal of Research and Studies, 2023)
The meaning vary according to their term,and this research paper aims to determine the relationship between the terms imagination and Imaginary,what are the implications of the use of these tow term in ancient greek philosophy,arab islamik philosophy,and ancient arab criticism?.were these terms efective in crystallizing the concepts of poetry,and creativity in the arab critical and philosophical heritage?.